Use of Technology in Tax Administrations 2 : Core Information Technology Systems in Tax Administrations - Cotton, Margaret (Technical Notes and Manuals; Technical Notes and Manuals ;, 2017)
This technical note is the second of three addressing information technology (IT) themes and issues relevant to tax administrations. This note addresses how to select a suitable IT system for core tax administration functions. Note one covers the use of IT in tax administrations and how to develop an information technology strategic plan (ITSP). The third note focuses on implementation of a commercial-off-the-shelf (COTS) system. These technical notes are primarily for tax administrations that have no technology to manage their core tax processes, or their technology is limited and outdated. These notes focus on core tax functions and do not address other business systems (e.g., payroll, finance, document, and asset management systems).